Counselling of Supplementary Feeding and Nutrition - Dewi, Mustika Sari (CV. Rayyan Dwi Bharata, 2025)
Background: Supplementary Feeding Programme is well known as the most common type of nutritional intervention in humanitarian response to prevent malnutrition. Another crucial intervention is nutrition education. The aims of the literature review are to asses the effectiveness of additional feed programme in increasing children growth and evaluate nutritional educational as another nutritional intervention that are able to reduce malnutrition cases in young children. Method: The MEDLINE and COCHRANE databases were accessed by searching researches that uses systematic review of all randomized controlled trials or randomized controlled trial from year 2000 until 2008. Just few journals use cohort study and case controlled study. The search was restricted to group of children less than five years old due to the largest target group in Supplementary feeding programme. Result: Food supplementation may have resulted in a modest increase in weight gain, but did not significantly improve length gain (Bhandari et al, 2001) similarly. On the other hand, based on four randomised controlled trials evaluating supplementary feeding in children aged 0-5 years old in developing countries, no firm conclusions of the benefits of supplementary feeding to the growth of pre-school children could be drawn (Sguassero et al, 2005). Malekafzali (2000) and Roy et al (2007) found that nutrition education successfully prevented malnutrition. Conclusion: Complementary feeding must be followed by educational intervention to acquire the best result. In emergency phase, it is better to give supplementary feeding to prevent children health status drop at malnourished condition due to limited food supply and risk of infection because contaminated water resources. However, it still needs accompanied by educational nutrition or counselling to mothers to make the impact more sustain.